2018
DOI: 10.1158/2326-6066.cir-18-0014
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy Using Ruxolitinib and Oncolytic HSV Renders Resistant MPNSTs Susceptible to Virotherapy

Abstract: Malignant peripheral nerve sheath tumors (MPNSTs) are aggressive soft-tissue sarcomas resistant to most cancer treatments. Surgical resection remains the primary treatment, but this is often incomplete, ultimately resulting in high mortality and morbidity rates. There has been a resurgence of interest in oncolytic virotherapy because of encouraging preclinical and clinical trial results. Oncolytic herpes simplex virus (oHSV) selectively replicates in cancer cells, lysing the cell and inducing antitumor immunit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 52 publications
(65 reference statements)
2
32
0
1
Order By: Relevance
“…Pre-treatment with Ruxolitinib enhanced the viral replication of oncolytic Herpes Simplex Virus (oHSV) in malignant peripheral nerve sheath tumours. Pre-treatment of mice with Ruxolitinib reduced Interferon stimulated genes expression making the tumours susceptible to oHSV infection [42]. Combination of Ruxolitinib and oncolytic vesicular stomatitis virus therapy resulted in enhanced oncolysis and viral replication in non-small cell lung cancer [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-treatment with Ruxolitinib enhanced the viral replication of oncolytic Herpes Simplex Virus (oHSV) in malignant peripheral nerve sheath tumours. Pre-treatment of mice with Ruxolitinib reduced Interferon stimulated genes expression making the tumours susceptible to oHSV infection [42]. Combination of Ruxolitinib and oncolytic vesicular stomatitis virus therapy resulted in enhanced oncolysis and viral replication in non-small cell lung cancer [41].…”
Section: Discussionmentioning
confidence: 99%
“…Combination of oncolytic viruses with immune checkpoint inhibitors and targeted therapies has been proven to be a successful strategy to enhance the efficiency of therapy response to oncolytic virus [39,40]. There are studies showing that targeting the JAK-STAT pathway in combination with the oncolytic herpes simplex virus and vesicular stomatitis viruses could enhance their efficiency possibly by modulating IFN signalling [41,42]. Hence, in this study we investigated also the effects upon combining oncolytic adenovirus with STAT3/5 inhibitors in bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Whole viruses are also under investigation as new approaches to treating cancer, a field referred to as viral oncolytics, in which viruses selectively target and kill cancer cells as well as enhancing natural immune cell killing of cancer cells [5,6]. Adenoviruses, herpesviruses, measles, senecavirus and poxviruses, such as vaccinia and myxoma, are all in active development as treatments for many cancers, including multiple myeloma, melanoma, sarcomas and brain cancers such as glioblastoma multiforma (GBM) [7][8][9][10][11]. The rabbit-derived myxomavirus is one such virus now demonstrated to selectively target, infect and kill cancer cells, without infecting or killing normal, noncancerous mammalian and human cells [6].…”
Section: Introductionmentioning
confidence: 99%
“…Short- 63 The combination of ruxolitinib and HSV to treat malignant peripheral nerve sheath tumour allografts in mice lead to enhanced virus replication, increased numbers of tumour-associated CD8 + T cells and prolonged survival compared to mice that were treated with HSV alone. 64 Similarly, in glioblastoma cells either pretreated with ruxolitinib or treated up to 12 hours after measles virus inoculation, STAT phosphorylation was decreased and virus replication was increased. 65 The drug is not listed for use in dogs; however, a recent study indicated that in vitro canine mast cell proliferation is inhibited by ruxolitinib treatment.…”
Section: Type I Ifns and Ovsmentioning
confidence: 99%
“…A laboratory studying VSV as an OV in pancreatic carcinomas observed the inhibition of STAT1/2 phosphorylation, decreased IFN‐stimulated genes (ISGs) and enhanced virus replication in cancer cells treated with ruxolitinib . The combination of ruxolitinib and HSV to treat malignant peripheral nerve sheath tumour allografts in mice lead to enhanced virus replication, increased numbers of tumour‐associated CD8 + T cells and prolonged survival compared to mice that were treated with HSV alone . Similarly, in glioblastoma cells either pretreated with ruxolitinib or treated up to 12 hours after measles virus inoculation, STAT phosphorylation was decreased and virus replication was increased .…”
Section: Type I Ifns and Ovsmentioning
confidence: 99%